Investigation of cigarette, alcohol and pathological gambling addiction in persons subject to probation measures - Pazarcıkcı, Mine; Altıntoprak, A. Ender (Journal of Dependence, 2020)
Objective: The aim of this study was to determine drug use characteristics and search prevalance of cigarette, alcohol and pathological gambling addiction on people subject to probation order due to article 191 of the Turkish Penal Code. Method: The sample of the study included 500 people is chosen by random sampling method among individuals over 18 and referred to İzmir Probation Branch. Personal Information Form, Fageström Nicotine Dependence Test, Alcohol Use Disorders Identification Test and The South Oaks Gambling Screen are used as data gathering tool. Results: Most common drug used lifetime was cannabis (88.2%). Mean age to start drug use 19.09±5.3, average drug use period is 6.3±7 years. The lifetime prevalence of smoking was 93% and the rate of ongoing use was 80.4%; lifetime alcohol use rate is 83%, current use rate is 67.4%; 2.2% had gambling disorder. There is a statistically positive correlation between level of substance use and smoking, alcohol use level and gambling behavior Conclusion: This data study can contribute to the development of rehabilitation and treatment programmes currently being implemented by addressing the addiction in an integrated framework.